Financial Behavior Dynamics of MSME Actors: A Contemporary Islamic Financial Management Study on Literacy, Attitude, Intention, Personality, and Legal Aspects - Muhammad Sulhan; Heri Pratikto; Imam Mukhlis; Puji Handayati; Muhammad Irfanul Hakim Zain (Faculty of Sharia, IAIN Metro, 2025)
This study explores the dynamics of financial behaviour among Micro, Small, and Medium Enterprises (MSMEs) within the framework of contemporary Islamic financial management. It focuses on analyzing the relationship between financial literacy, attitudes toward Islamic finance, intention to manage finances in line with Sharia principles, and the influence of personality traits on financial decision-making. Using a quantitative survey involving MSME actors from various industry sectors, the research finds that while overall financial literacy remains relatively low, most respondents possess a basic understanding of Islamic financial principles. Higher levels of financial literacy—especially in areas like cash flow and investment—are positively linked to effective financial management. A positive attitude toward Islamic finance also enhances MSME actors' intention to apply Sharia-compliant practices in their business operations. Those who value Islamic financial principles tend to manage debt more responsibly and avoid non-compliant financial behaviour. The study further shows that intention plays a central role in shaping Sharia-aligned financial practices. MSME actors with strong Sharia-based financial intentions are more open to using Islamic financial instruments and participating in related educational programs. Personality traits, particularly openness and conscientiousness, are found to significantly influence the likelihood of adopting Islamic financial practices, whereas closed or less detail-oriented individuals face greater challenges. This research contributes to the broader literature on Islamic financial management by offering insights into the behavioural factors influencing MSME financial practices and providing practical implications for strengthening Islamic financial literacy and implementation in the MSME sector.